Persepktif Tenaga Kesehatan pada Budaya Keselamatan Pasien - Meki Pranata; Siti Roifah; Muhammad Nurul Hasanudin (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2023)
Patient safety culture is a system that must be carried out by health workers as an effort to reduce unwanted events. Patient safety culture is a variable used to measure the implementation of patient safety. This study aims to determine the relationship between the demographics of health workers on the implementation of patient safety culture. This research is an analytic observational research using a cross sectional design. The respondents of this study were 120 respondents which were divided into 2, namely 35 respondents for validity and reliability tests and 85 respondents for the research sample. The research data collection was carried out in August-September 2021 at the Pati Regency Islamic Hospital using a questionnaire from the Agency for Healthcare Research and Quality. Data analysis used Eta correlation test and Chi-square test. The results of the research on 85 research respondents on the Eta correlation test and the chi-square test showed that the marital status of health workers had a low relationship with patient safety culture with a correlation value of 0.312 with a significance value of p <0.05.